First record of the genus Oliparisca Emeljanov (Hemiptera: Fulgoroidea: Cixiidae) from China, with description of one new species - Zhi, Yan; Yang, Lin; Chen, Xiang-Sheng (Zootaxa, 2020)
Oliparisca menglaensis sp. nov. (Hemiptera: Fulgoromorpha: Cixiidae: Pentastirini) is described and illustrated from Yunnan Province of China. This represents the first record of the genus Oliparisca from China. The new taxon extends the distribution range of the genus Oliparisca, previously known only from Indonesia, Malaysia, Philippines and Sri Lanka. A key of identification to all known species of this genus and a map of their geographic distributions are provided.